Analysis of the Movement of ICD Leads During Cardiac Contraction as Determinant of Intracardiac Impedance - Kirchner, Jens; Fischer, Georg; Arnold, Martin (2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2018)
Intracardiac impedance (ICI) has been proposed as an indicator of cardiac status in heart failure patients. We introduce a biophysical model of the measurement setup and apply it to the movement of ICD leads reconstructed from clinical-routine X-ray recordings in a study population of 12 patients. Tilting of the right ventricular lead is found to be a major determinant of ICI changes during cardiac contraction with a mean contribution of 42+-23%. The relative position between right and left ventricular lead is the second major contributor (40+-22%). However, the contributions of the components of movement strongly differ between the patients. The proposed method provides means for a better interpretation of ICI measurements and for an improvement of its performance for monitoring heart failure statu